Massive Scrotal Hematoma due to Ruptured Anastomotic Pseudoaneurysm in a Patient with Aortobifemoral Bypass Surgery: CTA Evaluation - Magdalini Smarda; Dimitrios Fagkrezos; Ilias Dodos; Anastasios Potouridis; Dimitrios Staramos; Charikleia Triantopoulou; Petros Maniatis (Case Reports in Vascular Medicine)
A 74-year-old male patient was presented with scrotal swelling and a pulsatile mass of the left femoro-inguinal region. His medical history included hypertension, coronary artery disease, respiratory failure, and an aortobifemoral bypass surgery performed 7 years ago. Ultrasound evaluation revealed a massive scrotal hematoma. Computed tomography angiography (CTA) was conducted, confirming the aortobifemoral graft existence and revealing bilateral anastomotic pseudoaneurysms with the left one being ruptured, resulting in extension of the hematoma to the left femoro-inguinal region and the scrotum. An emergency surgery was performed, where proximal control of the left limb of the synthetic graft as well as distal control of the iliac vessels were accomplished. After the control of the hemorrhage, an iliofemoral bypass with a Polytetrafluoroethylene (PTFE) 6 mm synthetic graft was placed. Unfortunately, the patient passed away during the first postoperative day due to myocardial infarction.